PENGEMBANGAN MEDIA KOTPEN (KOTAK PENGETAHUAN) BERBANTUAN AI PADA MUATAN IPAS KELAS IV DI SEKOLAH DASAR - Nabius, Riski; Abdullah, Gamar; Isnanto, Isnanto; Saleh, Meylan; Arif, R. Mardian (STKIP Melawi, 2024)
Abstract: This study aims to develop the KOTPEN (Knowledge Box) learning media assisted by AI for the Integrated Science and Social Studies (IPAS) subject in the 4th grade of elementary school. The research method used is a development research method with the ADDIE model. Based on validation results from experts and users, the Kotpen media received an average percentage score of 93.6% and was deemed highly suitable for use by teachers and students in elementary schools. In the practicality test of the Kotpen media, the researcher used a teacher observation sheet instrument, and the total score obtained was 38 out of a maximum score of 40, with an average score of 95%. Thus, the practicality percentage of using Kotpen media in learning reached 95%, which falls into the